Diversifying Employability Skills of The English Literature Students - Alamsyah, Aam; Mutaat; Abidin, Zaenal; Arnelli; Adrallisman (International Journal of English and Applied Linguistics (IJEAL), 2026)
Employability has been a concern of both the workforce and higher education. Despite being extensively studied in higher education, very few studies have examined the English literature department. The present study aimed to identify the perceptions of employability and other relevant factors among literature department students, such as the English literature students' perceptions of their department, the potential gap between job relevance and their preferred jobs, the perceived essential subjects, and the employability skills that students need for future employment. The research method used in the present study was quantitative. Specifically, it used a questionnaire to collect the data from the participants. Sixty-five English students voluntarily participated in the survey research. The results indicated that the participants had positive perceptions of their department for securing future employment. Furthermore, teaching, translating, or interpreting positions were perceived as the most suitable jobs for English literature graduates. Nevertheless, the findings indicated the gap between the students' perceived job suitability and their career aspirations. Specifically, most participants aspired to pursue careers in general employment and office work rather than stereotypically relevant positions. Given the variety of career aspirations identified among students in the present study, college administrators are expected to diversify the employability skills for English literature students to avoid the potential mismatch between students' dream jobs and the perceived stereotypical jobs that most language colleges offer.